2008
DOI: 10.1007/s00467-007-0585-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-steroidal anti-inflammatory drugs-associated acute interstitial nephritis with granular tubular basement membrane deposits

Abstract: Acute tubulo-interstitial nephritis (ATIN) is an important cause of acute renal failure resulting from a variety of insults, including immune complex-mediated tubulo-interstitial injury, but drugs such as non-steroidal anti-inflammatory drugs (NSAIDs) are a far more frequent cause. Overall, as an entity, ATIN remains under-diagnosed, as symptoms resolve spontaneously if the medication is stopped. We report on a 14-year-old boy who developed acute renal failure 2 weeks after aortic valve surgery. He was put on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 15 publications
1
21
0
1
Order By: Relevance
“…However, no specific infection could be identified in our patient. Although tubulointerstitial immune-complex nephritis is a very rare form of TIN, such nephritis can be caused by treatments such as nonsteroidal anti-inflammatory drugs [9], by autoimmune diseases such as lupus erythematosus [10], or IgG4-related diseases [11]. However, our patient received no long-term drug treatment apart from IVIG, and had no collagen disease or IgG4-related disease according to repeated laboratory examinations.…”
Section: Discussionmentioning
confidence: 95%
“…However, no specific infection could be identified in our patient. Although tubulointerstitial immune-complex nephritis is a very rare form of TIN, such nephritis can be caused by treatments such as nonsteroidal anti-inflammatory drugs [9], by autoimmune diseases such as lupus erythematosus [10], or IgG4-related diseases [11]. However, our patient received no long-term drug treatment apart from IVIG, and had no collagen disease or IgG4-related disease according to repeated laboratory examinations.…”
Section: Discussionmentioning
confidence: 95%
“…Permanently high resistance to antibiotics with increasing resistance rates of E. coli to ampicillin and TMP/SMX were shown in studies from the UK, Austria, Spain and Brasil [9,11,12,19 23]. Because of that, some authors concluded that ampicillin, trimetoprim, and TMP/SMX were insufficient for the monotherapy of UTI, as recommended by Wolff et al (2007) [9,24].…”
Section: Discussionmentioning
confidence: 99%
“…4 Drug-induced TIN with TBM immune complex deposition has been rarely documented in association with nonsteroidal anti-inflammatory drugs. 5 Polyclonal IgG and C3 TBM deposits are present without glomerular deposits. Two cases showed giant cell tubulitis with TBM deposits.…”
Section: Discussionmentioning
confidence: 99%